Clinical characteristics of hemodialysis patients with atrial fibrillation: The RAKUEN (Registry of atrial fibrillation in chronic kidney disease under hemodialysis from Niigata) study. Issue 2 (August 2016) - Mitsuma, Wataru; Matsubara, Taku; Hatada, Katsuharu; Imai, Shunsuke; Saito, Noriko; Shimada, Hisaki; Miyazaki, Shigeru
Abstract: Background: Clinical characteristics, management, and outcomes in hemodialysis patients with atrial fibrillation (AF) remain unclear. Methods and results: We studied 423 Japanese patients undergoing maintenance hemodialysis (age 65.2 ± 12.4 years, male 70%, mean duration of hemodialysis 139 ± 124 months). AF was present in 19% ( n  = 82) and was independently related to increased age (odds ratio 1.070, 95% confidence interval 1.043–1.098), longer hemodialysis duration (odds ratio 1.006, 95% confidence interval 1.004–1.008), and congestive heart failure (odds ratio 2.749, 95% confidence interval 1.546–4.891). During observations lasting a mean of 36 months, the incidences of all-cause death, cardiovascular death, and major bleeding, in particular gastrointestinal bleeding, were significantly higher in the AF ( n  = 82) than the non-AF ( n  = 341) patients ( p  < 0.001, p  = 0.004, p  = 0.002, p  = 0.027, respectively), but the incidence of ischemic stroke/systemic embolism was similar in the AF and non-AF patients. AF was independently associated with all-cause death (hazard ratio 1.728, 95% confidence interval 1.123–2.660) and major bleeding (hazard ratio 1.984, 95% confidence interval 1.010–3.896). Warfarin was prescribed in 33% of the AF patients, but the rates of all-cause death, ischemic stroke, and major bleeding during the study period were not significantly different between warfarin ( n  = 27) and non-warfarin ( n  = 55) groups. Conclusions: In our hemodialysis patients, AF was a common comorbidity and was independently associated with all-cause death and major bleeding, but not with increased risk of ischemic stroke.